Loss of highwire Protects Against the Deleterious Effects of Traumatic Brain Injury in Drosophila Melanogaster - Hill, Ciaran S.; Sreedharan, Jemeen; Loreto, Andrea; Menon, David K.; Coleman, Michael P. (Frontiers in Neurology, 2020)
Traumatic brain injury is a major global cause of death and disability. Axonal injury is a major underlying mechanism of TBI and could represent a major therapeutic target. We provide evidence that targeting the axonal death pathway known as Wallerian degeneration improves outcome in a Drosophila Melanogaster model of high impact trauma. This cell-autonomous neurodegenerative pathway is initiated following axon injury, and in Drosophila, involves activity of the E3 ubiquitin ligase highwire. We demonstrate that a loss-of-function mutation in the highwire gene rescues deleterious effects of a traumatic injury, including - improved functional outcomes, lifespan, survival of dopaminergic neurons, and retention of synaptic proteins. This data suggests that highwire represents a potential therapeutic target in traumatic injury.